Inventarisasi Tumbuhan Herbal di Kelurahan Batununggal, Daerah Sekelimus Utara, Buah Batu, Bandung, Jawa Barat - Puput Fuji Aslamiah; Rahadatul Aisyi Fatrisya Amdarsyah; Teges Lituhayu Syakirah; Ateng Supriyatna (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
The study was conducted on Sunday, June 09, 2024 in order to inventory and also identify plants that have potential as herbal plants in the thick of stone fruit in Bandung City, West Java province. this study aims to determine the types of plants that can be used as a natural traditional medicine. This study was conducted by going around the garden and identifying some of those identified using the PlantNet application, collecting data, and calculating the number of individuals, Diversity Index, dominance, evenness, and also wealth.From the results obtained as many as 14 plants that have the potential to become herbal plants, namely: Citrus aurantifolia, Mannihot esculenta, Carica papaya lin, Persea americana Mill, Aloe sp., Curcuma longa, Moringa olifera L., Cymbopogan nardus L., Magnifera indica L., Piper betle, Manilkara zapota (L), Artocarpus heterophyllus, Polyscias scutellaria, Solanum torvum Swartz.